Work and organizations - Webster, Edward (Oxford University Press, 2003)
The Introduction to Sociology series aims to present foundational sociology in a unique way and introduce students to current debates in the field. This book is an introduction to industrial sociology, its fundamental concepts and major writers, especially those relevant to southern Africa and the developing world